2004
DOI: 10.1097/01.ccx.0000139361.30327.20
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and critical care modeling

Abstract: Simulation models provide useful tools for organizing and analyzing the interactions between therapies, tradeoffs, and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Some research used machine learning algorithms, such as artificial neural networks and decision trees as a prediction algorithm in different critical care settings [22][23][24][25][26][27][28]. However, the evaluation of their performance is still under discussion.…”
Section: Q2mentioning
confidence: 99%
“…Some research used machine learning algorithms, such as artificial neural networks and decision trees as a prediction algorithm in different critical care settings [22][23][24][25][26][27][28]. However, the evaluation of their performance is still under discussion.…”
Section: Q2mentioning
confidence: 99%
“…30 Markov models require development of a series of states that must be mutually exclusive (a patient can be in only one state at a time) and collectively exhaustive (the patient has to be in one of the states at all times). 31 Patients move through the model according to probabilities that determine how likely it is to transition from one state to another over a specified period of time (the Markov cycle). Each health state is associated with a certain cost and health outcome for each cycle.…”
Section: Modeled Economic Evaluationsmentioning
confidence: 99%
“…To run the Markov model, individual patient cohorts cycle through the different states of the model based on the transition probabilities. 31 The model is run either for a fixed number of cycles or until all patients have entered an absorbing state (a state that they will remain in for all future cycles). 31 A simple characterization of a Markov model is shown in Fig.…”
Section: Modeled Economic Evaluationsmentioning
confidence: 99%
“…The authors of review [30] found that conventional modelling techniques used in critical care could be improved by simulation methods such as MCMC. They analysed the usefulness and limitations of applications of these methods presented in the related literature and concluded that simulation provided practitioners with additional information on risks.…”
Section: Simulationmentioning
confidence: 99%